An AIE‐based enzyme‐activatable fluorescence indicator for Western blot assay: Quantitative expression of proteins with reproducible stable signal and wide linear range. Issue 2 (7th February 2021) - Zhou, Tijian; Wang, Qi; Liu, Ming; Liu, Zhenxing; Zhu, Zhirong; Zhao, Xiaolei; Zhu, Wei‐Hong
Abstract: Western blot is a commonly used experimental method to analyze the protein expression. However, the most commonly used chromogenic indicator based on chemiluminescence is limited by narrow linear range and unstable quantitative reproducibility, whereas the recently developed fluorescent indicator suffers from poor detection limit. Herein, we report an enzyme‐activatable fluorescence indicator to quantify proteins with reproducible stable signal and wide linear range, through introducing the hydrophilic alkaline phosphatase (ALP)‐triggered phosphoric acid moiety into our established aggregation‐induced emission (AIE) building block of quinoline‐malononitrile (QM). In this strategy, the indicator DQM‐ALP disperses well in both aqueous and lipid environments to exhibit initial "off" fluorescence, but when exposing to the ALP‐coupled secondary antibody on the PVDF membrane, the specific enzymatic turnover would liberate hydrophobic AIE luminogen (AIEgen) QM‐OH to emit strong luminescence, thereby achieving an ideal "off‐on" state for sensitively imaging proteins with high signal‐to‐noise (S/N) ratio. Moreover, benefiting from the excellent signal stability of AIE fluorophore, DQM‐ALP indicator exhibits superior quantitative analysis of protein expression with high reproducibility. Upon taking advantage of the AIEgens to reduce high concentration‐induced luminance quenching, the linear quantification range is extremely expanded. In contrast with the traditional chemiluminescent indicator, the AIE‐based enzyme‐activatable indicator DQM‐ALP not only greatly improves the signal stability for quantitative reproducibility, but also expands the linear quantification range, and further provides a practical alternative reagent for fluorescence Western blot assay. Abstract : An AIE‐based enzyme‐activatable fluorescence indicator is designed and constructed to quantify proteins with reproducible stable signal and wide linear range in Western blot assay. The indicator DQM‐ALP disperses well in lipo/hydro environments to exhibit initial "off" fluorescence, but when exposing to the ALP‐coupled secondary antibody, specific enzymatic turnover would liberate hydrophobic AIEgen QM‐OH to emit strong luminescence.